Donald Creighton and the French Fact, 1920s-1970s - Wright, Donald (Journal of the Canadian Historical Association / Revue de la Société historique du Canada)

(untitled) (The Canadian Historical Association/La Société historique du Canada, 1995)
AbstractDonald Creighton is remembered as an anti-French bigot. Looking at his career in its entirety, this paper argues that such a caricature obscures a more complex story. As a historian, Creighton relied on a series of stereotypes - some negative, others positive - to describe and explain French Canada. In the 1960s and 1970s, his outdated stereotypes left him unable to understand Quebec nationalism. Although capable of intemperate remarks, Creighton's position was more thoughtful: for example, he distrusted devolution of powers to the provinces and he argued that French secondary schools in Ontario would render Franco-Ontarians second-class citizens, unable to compete in a labour market dominated by English.